Pemikiran Ibn Khaldun Tentang Rasionalisme Islam: Suatu Penelitian Ringkas - ahmad nabil amir (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2021)
This paper briefly discusses Ibn Khaldun’s philosophical and rational construction of Islam and its metaphysical discursus as set forth in his classical works such as kitab al-‘Ibar, Al-Ta‘rif, Tahrir al-Ahkam, and al-Muqaddimah. This works expressed his highly rational outlook that developed critical and rational understanding of religious and moral premises. It also summarized its dynamic ground that contribute to expound instructive discussion of related ideas and themes. The study is based on library research using content analysis and analyzed through analytical and descriptive approaches. The finding concludes that Ibn Khaldun has bring forth rational interpretation of history based on unique philosophical and socio-cultural analysis he introduced in his al-Muqaddimah. This characteristic approach of rational ideal has significantly impacted Islam’s modern history and tradition. His rational and argumentative principle has largely influence the works of contemporary Muslim thinkers such as Malik Bennabi, Rashid Ghannoushi and Muhammad Asad.